IMPLEMENTASI BEST PRACTICES PROGRAM RUMAH TANGGA MANDIRI PANGAN DAN ENERGI (RTMPE) DI KABUPATEN KAMPAR - Deni Agusta Putra; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Best Practices are defined as initiatives that have resulted in contributions prominent (outstanding contribution) in improving the quality better of life. The research objective to see the implementation of best practices program independent household of food and energy in kampar regency and to determine the factors that affect the implementation of best practices program independent household of food and energy in Kampar regency.Theoretical concept that researchers use are eko prasojo (2004:4) thereare three partnerships and sustainable impact. This research uses qualitative methods with an assessment of descriptive data. In the data collection reseachers use interviewing techniques, observation and documentation. By using purposive sampling method in which sample is designed by researchers and triangulation techniques as a source af data authenticity.The results showed that the implementers, implementation of best practices in independent households of food and energy in Kampar Regency not ranning optimally because there are still many obstacles in the implementatin, because there are many people who are not interested in implementing the program independent household of food and energy although mainstay programs Kampar Regency with the goal of three zero, zero proverty, zero unemployment and zero slum housing.Factors that hinder the implementation of best practices program independent household of food and energy in Kampar Regency (1) public’s understanding of the program (2) participation in the implementation of the program (3) the role of regent in the innovation program (4) a bureaucratic culture.Key Words : Implementasi , Best Practices, Program.